Two new species and a new record of the genus Spininola László, Ronkay & Witt, 2010 from China (Lepidoptera, Nolidae, Nolinae) - Huang, Zhen-Fu; Yu, Yong; Hu, Yan-Qing (Zootaxa, 2021)
Two new species (Spininola yongdingensis and Spininola qianfengensis spp. nov.) are described; Spininola denticulata (Moore, 1888) is reported from China for the first time. Adults and genitalia of new species are illustrated.